2005
DOI: 10.1353/pla.2005.0008
|View full text |Cite
|
Sign up to set email alerts
|

A Collaborative Model for Teaching E-Resources: Northwestern University's Graduate Training Day

Abstract: The authors report on the planning, execution, and future of Northwestern University's Introduction to Electronic Resources/Humanities Computing Training Day, a mandatory one-day set of classes for first-year doctoral students in humanities disciplines. The project is a collaborative effort among the Office of the Dean of the Weinberg College of Arts and Sciences; the University Library; and Academic Technologies. In this case study the authors explain the intricacies of the program and set it in the context o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Students who participated in the third year gave positive evaluations for the program. Also in the third year, doctoral students in the social sciences were included in the program (Lightman and Reingold 2005).…”
Section: Multiple Disciplinesmentioning
confidence: 99%
“…Students who participated in the third year gave positive evaluations for the program. Also in the third year, doctoral students in the social sciences were included in the program (Lightman and Reingold 2005).…”
Section: Multiple Disciplinesmentioning
confidence: 99%
“…A synthesis of the published research shows that studies on the information‐seeking behaviour of graduate students can be classified into three broad approaches, as follows:Information literacy approach (e.g. Hoffmann et al , 2008; Rempel and Davidson, 2008; Chu and Law, 2008; Hooks and Corbett, 2005; Lightman and Reingold, 2005). These studies either have either implications for enhancing the information literacy skills of graduate students; or are exclusively dedicated to exploring information literacy in relation to information‐seeking behaviour.Use of resources approach, which focuses on how users deal with electronic information resources in terms of searching behaviour and interactions with either the web or with a specific database.…”
Section: Introductionmentioning
confidence: 99%
“…Gold (2003) described the University of California, San Diego (UCSD) library's effort to unite various campus groups including the campus courseware services of the academic computing services to support the creation of an electronic text reserve service. Similarly, Lightman and Reingold (2005) reported that Northwestern University's graduate training day represented a collaboration among campus information technology professionals, librarians, administrators, and humanities faculty to address "the gap between teaching research skills and computer skills" (25).…”
Section: Discussion: the Internship And Its Implications For Communitmentioning
confidence: 99%